2018
DOI: 10.1002/ijfe.1615
|View full text |Cite
|
Sign up to set email alerts
|

Financial constraints and productivity: Evidence from euro area companies

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 79 publications
(114 reference statements)
9
89
0
Order By: Relevance
“…From an empirical viewpoint, existing studies generally confirm that firms in developing countries often cite financial constraints as the main obstacle to their growth [3][4][5][6][7]. However, some evidence suggests that the development of the financial sector may not necessarily lead to a positive outcome in terms of growth for firms [8][9][10][11]. Therefore, it is essential to study the impact of financial accessibility on firm growth, and investigate whether or not firms' access to external finance can improve their performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From an empirical viewpoint, existing studies generally confirm that firms in developing countries often cite financial constraints as the main obstacle to their growth [3][4][5][6][7]. However, some evidence suggests that the development of the financial sector may not necessarily lead to a positive outcome in terms of growth for firms [8][9][10][11]. Therefore, it is essential to study the impact of financial accessibility on firm growth, and investigate whether or not firms' access to external finance can improve their performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, higher capital intensity and technical progress embodied in new equipment will also have a positive influence on productivity. From the empirical viewpoint, most of the relevant existing studies conclude that better access to finance boosts firms' productivity [11,[13][14][15]. Furthermore, it was shown that many productive firms were not able to expand or make the technological improvements and investments needed to increase their productivity because they have no access to credit [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out in the previous passage, SMEs face numerous potential constraints that determine SMEs' capability to innovate. Nonetheless, literature tends to focus on the lack of credit as a sole indicator of external constraints [19][20][21][22]. Studies that deal with other types of constraint tend to focus on firms in developed markets [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Levine and Warusawitharana (2014) examined firms in four European countries and found a positive relationship between finance and future productivity growth at the firm level. Butler and Cornaggia (2011) found similar evidence that increased productivity is an important channel through which finance affects economic growth (see also Ferrando and Ruggieri 2015). There is also a notion that productivity growth largely takes place at the 6 extensive margin-that is, the creation of new firms and closure of unproductive firms-rather than at the intensive margin, which involves firms becoming more productive internally (Kerr and Ramana 2009).…”
Section: Resultsmentioning
confidence: 80%